Prevent strategy: helping the vulnerable being drawn towards terrorism or another layer of state surveillance? - Lowe, David; Bennett, Robin (Routledge advances in sociology, 2021)
"Prevent Strategy is a collection of work from practitioners (youth workers and the police) and academics researching Prevent covers overcoming the stigma attached to Prevent being implicitly racist, problems related to the section 26 duty, training staff on Prevent, creating safe spaces to have open discussions, problems regarding extremists' online activity and the law surrounding freedom of expression. Since its introduction the UK's Prevent strategy has been surrounded with controversy ranging from making the Muslim community a dangerous 'suspect community' to being another layer of police surveillance on individuals who have not been arrested or convicted of a crime. Despite amendments having to the strategy that now covers all forms of extremism and in adopting a multi-agency approach these suspicions remain, exacerbated by the section 26 Counter-Terrorism and Security Act 2015 duty to prevent vulnerable people being drawn towards terrorism. The knowledge, views and findings on the Prevent strategy from the respective contributors will appeal to all staff in education, health service and criminal justice agencies who carry out the section 26 duty and academics and students studying the area of terrorism and security"--